Pendidikan Kewirausahaan dan Sosial Ekonomi Terhadap Minat Berwirausaha - Muhammad Irfan Nasution; Khairun Nisa (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
The purpose of this study was to analyze the influence of entrepreneurship education, socio-economics, on the entrepreneurial interest of undergraduate students at the Muhammadiyah University of North Sumatra. The sample used was 95 people. This study uses incident sampling techniques and data collection using questionnaires. The data analysis technique used is data validity test, reliability test, classical assumption test, multiple linear regression, t-test, f-test and determinant coefficients. The results of the study show that partially entrepreneurship education has a significant effect on interest in entrepreneurship. Socio-Economic also has a positive and significant influence on Entrepreneurial Interest. Simultaneously, it is known that entrepreneurship education and socio-economic status on entrepreneurial interest have a positive and significant effect on entrepreneurial interest in North Sumatra Muhammadiyah University students.